Responsible Leadership and Sustainable Performance: The Roles of Pro-Environmental Behaviour and Digital Culture in IT Companies - Dhungana, Madan; Shakya, Suzil (Journal of Business and Social Sciences Research, 2025)
This study investigates the relationship between responsible leadership, pro-environmental behaviour, sustainable performance, and digital culture in selected IT companies. It aims to assess the current state of these aspects in the given situation. Furthermore, the study focuses on the direct influence of responsible leadership on sustainable performance. Moreover, it examines the mediating roles of pro-environmental behaviour and digital culture in shaping the relationship between responsible leadership and sustainable performance. The study employs causal and explanatory research methodologies to investigate the relationship between responsible leadership, pro-environmental behaviour, sustainable performance, and digital culture in IT companies. A cross-sectional design was used to collect data from 403 employees across eight (8) IT firms in the Lalitpur district of Nepal. A 5-point Likert-scale questionnaire was administered to collect responses. The study used correlation and regression analyses, as well as mediation analysis through Hayes Process Macro. Findings reveal a strong positive correlation among responsible leadership, digital culture, pro-environmental behaviour, and sustainable performance. Achieving superior, sustainable, and accountable performance requires setting clear ecological goals, encouraging employee involvement, and maintaining operational transparency.